KOTA PINTAR ALA AL-FARRABI: STUDI KRITIS FILSAFAT POLITIK AL- FARRABI - Muqsith, Awal (Jurnal Politik Profetik, 2017)
Structure of an ideal state, according to al-Farraby, is similar to that of a human body by which all parts support each other in achieving perfection and collectively working in preserving life. Al-Farraby believes that the entire universe is an emanation of the first being. Quoting the words of Ahmad Musayyar, "al-Farraby is a disciple of wahdawy, who believes in the unity of creator, universe, human beings, society, power of thought and philosophy." Based on wahdawy paradigm, al-Farraby established his idea of a state. In his analogy, al-Farraby constructed a social interdependent community. The unity is a reflection of a rhythmic beauty of the symphony of the well-organized, thorough and meticulous universe. The unity of the universe is an inspiration for the scientific paradigm, ideology and particularly to the constellation of the state of human beings. Thus, this is the framework to establish a smart polis, an ideal state.